A case analysis for Kubernetes network security of financial service industry in Indonesia using zero trust model - Nico Surantha; Felix Ivan; Ritchie Chandra (Institute of Advanced Engineering and Science, 2023)
In this study, a case analysis of Kubernetes application in an enterprise providing financial services in Indonesia is presented. It is implemented to improve their digital services-based application, developed using micro-services architecture. Kubernetes, an application container technology, has been applied in the enterprise providing financial services in Indonesia to improve their digital services-based application, developed using micro-services architecture concepts. Without incorporating any additional hardware, the new technology and services have been adopted to existing virtualized resources of the enterprise. An infrastructure design for secure Kubernetes networking was built and has been studied using the data center provided by the enterprise. This study focuses on two important aspects: network and security. As a security guideline, the network recommendations from VMware, Cisco, and Forrester’s zero trust model were employed to design the infrastructure and were evaluated. The proposed secure network infrastructure design is successfully applied in the container networks using the zero trust requirement, the enterprise’s requirements, and constraints. And we hope this study about network design security can be used and adaptable with existing network and reduce risk and disruption to the business caused by the network.